2018
DOI: 10.1525/mp.2018.35.3.332
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Listening and Timbre

Abstract: TIMBRE PLAYS AN ESSENTIAL ROLE IN TRANSMIT-ting musical affect, and in recent years, our understanding of emotional expression in music has been enriched by contributions from the burgeoning field of embodied music cognition. However, little attention has been paid to timbre as a possible mediator between musical embodiment and affect. In three experiments, we investigated the embodied dimensions of timbre perception by focusing on timbral qualities considered ''noisy'' and aversive. In Experiment 1, participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 120 publications
(180 reference statements)
0
18
0
2
Order By: Relevance
“…That is, conscious deliberation diverged from implicit association. Moreover, certain timbre–semantic relationships are probably influenced by valence transfer (Weinreich & Gollwitzer, 2016): for example, the association between aversive growled saxophone and “dark” likely relates more to negative valence than vision, since the growl timbre is actually quite “bright” in terms of spectral distribution (see also Wallmark et al, 2018). This suggests that, at least in certain instances, synesthetic congruity is modulated by cultural context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, conscious deliberation diverged from implicit association. Moreover, certain timbre–semantic relationships are probably influenced by valence transfer (Weinreich & Gollwitzer, 2016): for example, the association between aversive growled saxophone and “dark” likely relates more to negative valence than vision, since the growl timbre is actually quite “bright” in terms of spectral distribution (see also Wallmark et al, 2018). This suggests that, at least in certain instances, synesthetic congruity is modulated by cultural context.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, if valid, the ecological perspective might complicate this account, implying that identification and meaning are mutually entwined and roughly synchronous (Clarke, 2005;Gaver, 1993;Gibson, 1966). For example, corroborating this view, recent neuroimaging data suggest that perception of aversive timbres commonly described with negative texture metaphors ("harsh," "rough") activates regions of the secondary somatosensory cortex also responsible for processing tactile sensation (Wallmark, Iacoboni, Deblieck, & Kendall, 2018; see also Schu ¨rmann, Caetano, Hlushchuk, Jousma ¨ki, & Hari, 2006).…”
mentioning
confidence: 84%
“…More generally, Halpern et al (2004) observed subthreshold activity in supplementary motor area (SMA) during timbre imagery tasks. Wallmark et al (2018) demonstrated a motor component to timbre perception; they interpret their results as indicating a possible propensity to link timbral qualities with associated actions.…”
Section: Motor Imagerymentioning
confidence: 90%
“…For example, listeners’ arm movements while listening to music played on a traditional Chinese plucked string instrument matches the pattern of movements of the performers’ shoulders (Leman et al, 2009). Several brain areas associated with music perception are also associated with vocalizing and motor planning (Brown & Martinez, 2007; Callan et al, 2006; Chen et al, 2008; Miller, 2016); and brain motor planning areas are activated during music listening (Gordon et al, 2018; Wallmark et al, 2018), especially in musicians (Alluri et al, 2017). Subvocalization (subtle movements of muscles related to vocal production) has been observed during musical mental imagery tasks (Pruitt et al, 2019;—but not during listening: Bruder & Wöllner, 2021).…”
mentioning
confidence: 99%